Pengaruh Faktor Lingkungan Sosial terhadap Perilaku Self-harm pada Remaja - Fadhilah, Najiyah Nur; Hermawan, Aisyadinandya; Al-Gifari, Achmad Hafiz; Kusmawati, Ati (Universitas Mathla'ul Anwar Banten, 2025)
This study looked at how the social environment influenced adolescents' self-harm behavior. The high number of self-harm cases among teenagers is a major problem. This is due to social pressures such as disharmonious families, negative associations, and the stigma of society on mental health. The purpose of the study was to find out how social factors led to self-harm behavior and to find a successful intervention solution. The method used is to conduct literature research by looking at 15 relevant sources from Google Scholar published in the last ten years. Research results show that unsupportive social environments, such as lack of open communication in the family, academic pressure, and poor peer influence, play a major role in inducing self-harm. On the other hand, strong social support from family, school, and society can be a protective factor. In conclusion, self-harm management requires a holistic approach that involves improving the social environment, mental health education, and active participation of adolescents in prevention programs.